Pedagogical Innovation In BaPedagogical Innovation In Basic Education: A Systematic Reviewsic Education: A Systematic Review - Flores Carrasco, Alex (2024)
Traditional teaching methods in basic education are not very relevant and the expected results are not achieved, we live in a world of constant change with the advances of science and technology, therefore the good performance of students depends on many factors, one of them is the pedagogical innovation to apply, with the use of various means and concrete materials or tics. This systematic review research article aims to analyze and systematize research articles about pedagogical innovation in basic education. For this systematization of the work, the search and selection of many research articles is used, applying the PRISMA flowchart, this strategy allows us to select relevant articles that are related and justified with the topic to be dealt with in the present investigation. The results They show us selected articles in three thematic fields, one of them is the use of various active methodological strategies where many authors agree on their conclusions, then the use of different ICT tools and devices supported by authors where they agree with their conclusions and also another group of authors argue that ethical leadership prevails over pedagogical leadership. It is concluded that the use of various active methodological strategies, with the support of ICT tools and devices, plus the ethical leadership of the teacher, generates pedagogical innovation in educational work.